The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.asmr.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Multimodal Pain Management and Opioid Consumption in Arthroscopy Clinical Trials: A Systematic Review

Abstract: Purpose: To provide an updated review of multimodal pain management in arthroscopic surgery by evaluating pain and opioid consumption after shoulder, knee, and hip arthroscopy. Methods: A comprehensive literature search was performed to identify randomized controlled trials (RCTs) investigating multimodal pain management after shoulder, knee, and hip arthroscopy. Articles were identified from January 2011 through December 2020 using various databases. As the primary outcome variables of this study, differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
0
4
0
1
Order By: Relevance
“…Third, this study only included the use of adjunctive oral medications and did not include the use of regional anesthesia (aside from peri‐incisional local anesthetic infiltration). However, prior systematic reviews have only reported a significant improvement in pain and reduction in opioid use in a single included clinical trial evaluating the efficacy of femoral nerve blocks in hip arthroscopy; however, this does carry an associated risk of falls [21, 31]. Further study is required of adjunctive regional anesthesia techniques to determine if alternative blocks may provide improved pain control without added perioperative risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study only included the use of adjunctive oral medications and did not include the use of regional anesthesia (aside from peri‐incisional local anesthetic infiltration). However, prior systematic reviews have only reported a significant improvement in pain and reduction in opioid use in a single included clinical trial evaluating the efficacy of femoral nerve blocks in hip arthroscopy; however, this does carry an associated risk of falls [21, 31]. Further study is required of adjunctive regional anesthesia techniques to determine if alternative blocks may provide improved pain control without added perioperative risk.…”
Section: Discussionmentioning
confidence: 99%
“…While reducing opioid prescriptions is essential, effective pain management is important to improve patient satisfaction and clinical outcomes, particularly when considering ambulatory surgical procedures where successful discharge and avoidable readmissions are tied to the adequacy of postoperative analgesia [1]. The use of multimodal analgesia to improve pain control is gaining significant attention, particularly in sports medicine, with recent publications demonstrating efficacy in shoulder and knee surgery [10, 16, 21]. However, its use and efficacy in hip arthroscopy are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Patients returning to pharmacies for prescription renewal or acquisition of step-down medication may be targets for these interventions. Importantly, multimodal pain management strategies are proving effective in reducing postoperative opioid consumption in the orthopedic setting [16]. When combined with a multimodal strategy, point-of-service disposal interventions may further mitigate the risk of diversion of unused opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of patients who had undergone TKA, nonpharmacological interventions were associated with moderate improvement in pain (Komann et al, 2019). Despite limited outcome data, the promotion of postoperative care that includes both passive and active interventions have demonstrated value (Cheah et al, 2022; Fan & Chen, 2020; Komann et al, 2019; Paul et al, 2021; Tedesco et al, 2017).…”
Section: Recommendations For Each Phase Of Carementioning
confidence: 99%